Decreased free D-aspartate levels in the blood serum of patients with schizophrenia - Garofalo, Martina; De Simone, Giuseppe; Motta, Zoraide; Nuzzo, Tommaso; De Grandis, Elisa; Bruno, Claudio; Boeri, Silvia; Riccio, Maria Pia; Pastore, Lucio; Bravaccio, Carmela; Iasevoli, Felice; Salvatore, Francesco; et al. (Frontiers in Psychiatry, 2024)
Introduction: Schizophrenia (SCZ) and autism spectrum disorder (ASD) are neurodevelopmental diseases characterized by different psychopathological manifestations and divergent clinical trajectories. Various alterations at glutamatergic synapses have been reported in both disorders, including abnormal NMDA and metabotropic receptor signaling.We conducted a bicentric study to assess the blood serum levels of NMDA receptors-related glutamatergic amino acids and their precursors, including L-glutamate, L-glutamine, D-aspartate, Laspartate, L-asparagine, D-serine, L-serine and glycine, in ASD, SCZ patients and their respective control subjects. Specifically, the SCZ patients were subdivided into treatment-resistant and nontreatment-resistant SCZ patients, based on their responsivity to conventional antipsychotics.Results: D-serine and D-aspartate serum reductions were found in SCZ patients compared to controls. Conversely, no significant differences between cases and controls were found in amino acid concentrations in the two ASD cohorts analyzed.Discussion: This result further encourages future research to evaluate the predictive role of selected Damino acids as peripheral markers for SCZ pathophysiology and diagnosis.